Ah-33 The Effects of Ethanol Mahogany (Sweitenia mahagoni Jacq.) Seeds Extract on Antioxidant Superoxide Dismutase in the Liver Tissues of Diabetic Experimental Rats - Eka Prasetiawan; I Ketut Mudite Adnyane; Tutik Wresdiyati (Media Veteriner, 2015)
The Effects of Ethanol Mahogany (Sweitenia mahagoni Jacq.) Seeds Extract on Antioxidant Superoxide Dismutase in the Liver Tissues of Diabetic Experimental Rats